2019
DOI: 10.1039/c9nj03976g
|View full text |Cite
|
Sign up to set email alerts
|

A nitrogen and phosphorus enriched pyridine bridged inorganic–organic hybrid material for supercapacitor application

Abstract: A heteroatom-enriched hybrid material, HPHM, has been synthesized and it was used to demonstrate the role of mass loading in supercapacitor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…delocalize the total electron density of the framework by creating defects and acting as active sites for the substrate molecules. [61][62][63][64][65] The optical, electronic properties and chemical reactivity of nano-carbons can be tuned by the generation of ntype or p-type carriers. In addition, heteroatom doping can affect the water solubility and bandgap of nano-carbons.…”
Section: Effect Of Heteroatom Incorporationmentioning
confidence: 99%
“…delocalize the total electron density of the framework by creating defects and acting as active sites for the substrate molecules. [61][62][63][64][65] The optical, electronic properties and chemical reactivity of nano-carbons can be tuned by the generation of ntype or p-type carriers. In addition, heteroatom doping can affect the water solubility and bandgap of nano-carbons.…”
Section: Effect Of Heteroatom Incorporationmentioning
confidence: 99%
“…Figure a–c shows the cyclic voltammetry (CV) analysis of the MoS 2 nanosphere, Bio-C, and Bio-C/MoS 2 composite electrodes in a three-electrode system with an Ag/AgCl reference electrode in a 2 M Na 2 SO 4 electrolyte at various scan speeds (20, 40, 60, 80, and 100 mV s –1 ). It is reported that the increase in mass loading is directly linked to enhancement in specific capacitance in existing literature. , Here, it was pointed out that the negative effect of excessive mass loading provided only limited number of active sites and thereby reduced the overall displacement current on the electrodes. In this present work, it also has been observed that mass loading is positively related to improvements of the capacitive performances of the Bio-C/MoS 2 composite supercapacitor, which is evident from the CV measurement results in Figure a–c.…”
mentioning
confidence: 91%
“…Furthermore, carbon-based materials can have a wide range of features, including large surface area, structural stability, and excellent thermal as well as optical properties. Carbon-based materials with these beneficial properties are successful in a variety of applications including energy storage and fuel cells. Carbon-based materials are well-known for increasing the electrical conductivity, while also providing structural support to prevent metal oxide agglomeration . Several composites have been reported, such as MoS 2 /reduced graphene, aerogel, and MoS 2 /carbon nanotube (CNT) composites .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, adding different functional groups to another monomer molecule can effectively change the dipole size of the molecule and further copolymerize with cyclotriphosphazene to form polymers with different dipole abilities. [22][23][24][25] The polymer's strong dipoles enable spatially inhomogeneous distribution of charges and polarization of the polymer environment, which improves the generation and separation of photoexcited electron-hole pairs. 26 However, the specic mechanism of how the dipoles of the monomer molecules affect the photogenerated carrier transfer in polymers needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%